Pengaruh Return On Assets (Roa), Return On Equity(Roe) Dan Net Profit Margin(Npm) Terhadap Harga Saham Pada Perusahaan Manufaktur Food And Beverageyang Terdaftar Di Bursa Efek Indonesia (Studi Empiris Pada Perusahaan Manufaktur Sektor Food And Baverage Tahun 2012-2014) - Hidayah, Nur, Drs. Agus Muqorobin, M.M (2016)
The financial statements reflect a picture of the financial performance of a company. The purpose of this research is to prove empirically and analyze the influence of Return On Assetc (ROA), Rerurn On Equity (ROE) and Net Profit Margin (NPM) to the stock price on Food And Baverage manufacturing companies listed in Indonesia Stock Exchange. The population of this study was to determine the profitability of manufacturing companies Sector Food and Baverage in 2012-2014. Method of making up is a company in the manufacturing industry group listed on the Stock Exchange. The sampling is a group of companies in the manufacturing industry are listed on the Stock Exchange. Sampling was based on criteria that exist in the company whose shares are listed on the Stock Exchange for three consecutive years. The data used in this research is secondary data in the form of quantitative financial ratio data for 3 years from 2012-2014. And in count 5 days before and 5 days after the date specified. The data is taken in the Indonesia Stock Exchange (BEI). T-test research results show that the ROA (X1), and ROE (X2) has a significant influence on stock return (Y) individually, while NPM (X3) had no significant effect individually. So also from the results of the F test obtained no significant effect ROA (X1), ROE (X2), and NPM (X3) on stock returns (Y) together.